2002
DOI: 10.1128/aem.68.1.166-172.2002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Key Metabolites during Biodegradation of Hexahydro-1,3,5-Trinitro-1,3,5-Triazine with Rhodococcus sp. Strain DN22

Abstract: N]-RDX, the [M-H] appeared at 120 Da, indicating that two of the three N atoms in the metabolite originated from the ring in RDX. When [U-14 C]-RDX was used in the experiment, 64% of the original radioactivity in RDX incorporated into the metabolite with a molecular weight (MW) of 119 (high-pressure LC/radioactivity) and 30% in 14 CO 2 (mineralization) after 4 days of incubation, suggesting that one of the carbon atoms in RDX was converted to CO 2 and the other two were incorporated in the ring cleavage produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
176
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(191 citation statements)
references
References 28 publications
11
176
4
Order By: Relevance
“…strain DN22 produced the key ring cleavage product 4-nitro-2,4-diazabutanal (NDAB, NO 2 NHCH 2 NHCHO) representing 60% of C-content in RDX, carbon dioxide (30% detected as 14 CO 2 ), nitrous oxide (N 2 O) together with nitrite and ammonia. The C mass balance was approximately 90% (5). In the present study we incubated RDX with DN22 under aerobic conditions and found that the missing 10% C was due to the formation of methylenedinitramine (MEDINA, NO 2 NHCH 2 NHNO 2 ) which decomposed to HCHO and 2N 2 O (Figure 1).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…strain DN22 produced the key ring cleavage product 4-nitro-2,4-diazabutanal (NDAB, NO 2 NHCH 2 NHCHO) representing 60% of C-content in RDX, carbon dioxide (30% detected as 14 CO 2 ), nitrous oxide (N 2 O) together with nitrite and ammonia. The C mass balance was approximately 90% (5). In the present study we incubated RDX with DN22 under aerobic conditions and found that the missing 10% C was due to the formation of methylenedinitramine (MEDINA, NO 2 NHCH 2 NHNO 2 ) which decomposed to HCHO and 2N 2 O (Figure 1).…”
Section: Resultsmentioning
confidence: 52%
“…Rhodococcus sp. strain DN22, provided by N. V. Coleman, (University of Sydney, Sydney, Australia) was grown in mineral salt medium (MSM) supplemented with succinate (2.4 mM) as the carbon source (5). RDX (220 µM) or MNX (220 µM) was added as the sole nitrogen source from an acetone stock solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methylamine and dimethylamine were analyzed as described by Gui et al (2000). The capture and quantification of 14 CO 2 were performed as described previously (Fournier et al, 2002).…”
Section: Pathway Of Ndma Degradation By Pseudomonas Mendocina Kr1mentioning
confidence: 99%